Factors associated with the level of CD4 cell counts at HIV diagnosis in a French cohort: a quantile regression approach. (March 2017) - Bruneau, Léa; Billaud, Eric; Raffi, François; Hanf, Matthieu
The consensus definition of late presentation for human immunodeficiency virus patient based on a CD4 threshold of 350 cells/mm 3 has limitations concerning risk factors identification since there is growing biomedical justification for earlier initiation of treatment. The objective was to overcome this problem by simultaneously determining factors associated with different levels of CD4 counts at the time of diagnosis. Between January 2000 and July 2014, 1179 patients with a first human immunodeficiency virus diagnosis and entering care in a French human immunodeficiency virus reference center were enrolled. Factors associated with each 5 percentile from 5th to 95th quantile of CD4 counts at diagnosis were simultaneously studied in a multivariable quantile regression model. At each of the quantiles, the factors identified as negatively associated with CD4 count at diagnosis were older age, male sex, foreign patients, hepatitis B virus or hepatitis C virus co-infection, employment status, non-MSM transmission, heterosexual transmission, suburban and rural's place of residence and earlier period of diagnosis. Association with CD4 count was not uniformly significant, most factors being significant for some quantiles. The only significant determinant for all quantiles was being born in a foreign country. These results are particularly helpful in the context of human immunodeficiency virus clinical care, management and prevention.